Enzyme promiscuity drives branched-chain fatty acid synthesis in adipose tissues. (November 2018) - Wallace, Martina; Green, Courtney; Roberts, Lindsay; Lee, Yujung; McCarville, Justin; Sanchez-Gurmaches, Joan; Meurs, Noah; Gengatharan, Jivani; Hover, Justin; Phillips, Susan; Ciaraldi, Theodore; Guertin, David; et al.
Abstract Fatty acid synthase (FASN) predominantly generates straight-chain fatty acids using acetyl-CoA as the initiating substrate. However, monomethyl branched-chain fatty acids (mmBCFAs) are also present in mammals but are thought to be primarily diet derived. Here we demonstrate that mmBCFAs are de novo synthesized via mitochondrial BCAA catabolism, exported to the cytosol by adipose-specific expression of carnitine acetyltransferase (CrAT), and elongated by FASN. Brown fat exhibits the highest BCAA catabolic and mmBCFA synthesis fluxes, whereas these lipids are largely absent from liver and brain. mmBCFA synthesis is also sustained in the absence of microbiota. We identify hypoxia as a potent suppressor of BCAA catabolism that decreases mmBCFA synthesis in obese adipose tissue, such that mmBCFAs are significantly decreased in obese animals. These results identify adipose tissue mmBCFA synthesis as a novel link between BCAA metabolism and lipogenesis, highlighting roles for CrAT and FASN promiscuity influencing acyl-chain diversity in the lipidome. mmBCFAs are endogenous fatty acids synthesized from BCAAs by brown and white adipose tissue via CrAT and FASN promiscuity. BCAA catabolism and mmBCFA lipogenesis are decreased by obesity-induced adipose hypoxia and influenced by the microbiome.